2005
DOI: 10.1091/mbc.e05-01-0025
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of B Cell Receptor Internalization upon Conditional Depletion of Clathrin

Abstract: B cell antigen receptor (BCR) association with lipid rafts, the actin cytoskeleton, and clathrin-coated pits influences B cell signaling and antigen presentation. Although all three cellular structures have been separately implicated in BCR internalization, the relationship between them has not been clearly defined. In this study, internalization pathways were characterized by specifically blocking each potential mechanism of internalization. BCR uptake was reduced by ϳ70% in B cells conditionally deficient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
132
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(147 citation statements)
references
References 38 publications
(68 reference statements)
13
132
1
Order By: Relevance
“…Previously, we showed that BCR activation induced the recruitment of clathrin to the BCR and phosphorylation of clathrin within lipid rafts, both of which were required for BCR internalization (26). In this study, we found that BCR activation induced the recruitment of Abp1 to the plasma membrane and to the internalizing BCR, suggesting that BCR signaling regulates the function of Abp1.…”
Section: Discussionsupporting
confidence: 55%
“…Previously, we showed that BCR activation induced the recruitment of clathrin to the BCR and phosphorylation of clathrin within lipid rafts, both of which were required for BCR internalization (26). In this study, we found that BCR activation induced the recruitment of Abp1 to the plasma membrane and to the internalizing BCR, suggesting that BCR signaling regulates the function of Abp1.…”
Section: Discussionsupporting
confidence: 55%
“…The clathrin-dependent pathway has been shown to be the primary pathway for ligand-induced BCR endocytosis, and raft structures appear to be required for efficient phosphorylation of clathrin heavy chain [21,33]. Tyrosine-phosphorylation of clathrin heavy chain is induced by an SRC-type protein kinase in response to stimulation of various receptor types, and the level of phosphorylation correlates with the rate of receptor internalization [21,[34][35][36][37]. Our data support a requirement for phosphorylation of clathrin heavy chain as well as for that of other endocytosis-related factors in BCR internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Receptors remaining at the cell surface were detected by flow cytometry with a FACScan instrument (Becton Dickinson) or by confocal laser-scanning microscopy [21]. The percentage of cells with surface receptors was calculated and normalized by the corresponding initial value.…”
Section: Receptor Endocytosismentioning
confidence: 99%
“…Itch constitutively colocalizes with endophilin A1 and clathrin H chain (41). As internalization of the BCR is dependent upon clathrin (42), residence on these membrane-associated structures may be sufficient for Itch to ubiquitinylate the BCR.…”
Section: Discussionmentioning
confidence: 99%